The New World settlement as seen from different craniofacial morphospaces: An Evo-Devo approach - Galland, Manon (2016)
The arrival and dispersal of human populations in the Americas remains a very controversial issue especially regarding the number of migration waves. Craniofacial variation between ancient and recent Amerindians has been attributed to the effects of multiple founder events or alternatively, as the result of a single population carrying high levels of internal heterogeneity and effects of local differentiation plus recurrent gene flow. Here we investigated craniofacial shape variation of a large sample (978 specimens) of past and modern groups from America and Australasia applying 3D geometric morphometrics methods and the Factor Model. This approach enables to separate shape features that covary because of common factors from those only explained by local factors. We analyzed separately the full skull shape as well as neurocranium and face modules in both integrated and modular shape spaces. All analyses underlined a high variability among ancient specimens and show that regional factors explain most of the variance observed. These results give more support to the hypothesis of a relatively fluid and continuous variation than the presence of two distinct biological populations.